Efectos del Sistema General de Regalías y las finanzas departamentales en Colombia en el periodo de 2008 a 2016. (2017)
The implementation of the new General System of Royalties through Law 1530 of 2012 brought with it a series of modifications in the distribution of resources, consequently the territorial entities and specifically the departments were exposed to a new assignment where the whole of these have been benefited. Based on the above, the incidence of royalty resources in departmental finances is analyzed through the creation of a series of indicators. The document is divided into four sections, the first establishes the theoretical and empirical parameters of the investigation, the second exposes two panoramas of royalties, a historical overview and a general overview of the organization of the General Royalty System; the third section shows a series of graphs resulting from the operation of indicators related to departmental finances and the last section shows the use of a statistical tool (shift share) that evaluates the executions in investment projects with royalties from the department with the highest index of dependency of royalties in the years of validity of the General System.